Effect of Intervention on self-confidence levels among Rural Adolescent Girls during Covid-19 in Telangana State - Bari, Sana; Rani, G. Swarupa; Devi, M. Sarada; Reddy, R. Geetha (International journal of Rural Development, Environment and Health Research, 2021)
The COVID-19 pandemic and the associated measures has left many people with low self-confidence particularly the adolescents where they’ve been left alone as they have lost touch with their routine, friends and family, accompanied with uncertainty of exams and online classes affecting their wellbeing. Thus, the aim of this investigation was to evaluate levels of self-confidence and to know the effect of intervention on self-confidence levels among the rural adolescent girls during the COVID-19 pandemic. A sample of 60 rural adolescent girls were selected for the study. An experimental design was used with a self-confidence scale which was developed to measure the self-confidence levels of the rural adolescent girls during pre-test and post-test. The results of the study depicted that, the self-confidence levels of the majority of the rural adolescent girls were in average and low category during the pre-test has significantly improved to high category during the post-test. Further the findings also found the paired t-test value was 9.79** which indicates a high significant difference at 0.01 level of probability. Therefore, it was concluded from the results of the study that the intervention on self-confidence levels was effective during the COVID-19 pandemic.